1979
DOI: 10.1073/pnas.76.1.442
|View full text |Cite
|
Sign up to set email alerts
|

Generation of cytolytic T lymphocytes after reovirus infection: role of S1 gene.

Abstract: Cytotoxic T lymphocytes (CTLs) can be generated if spleen cells from reovirus-infected mice are stimulated in vitro with syngeneic reovirus-infected cells. These cytolytic effector cells demonstrate: (i) serotype specificity (i.e., maximal cytolytic activity is observed on target cells infected with the serotype used to induce the CTLs) and (ii) H-2 restriction. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
49
1

Year Published

1980
1980
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(53 citation statements)
references
References 28 publications
3
49
1
Order By: Relevance
“…Finberg and colleagues provided the first evidence that MHC-restricted, reovirus-specific cytotoxic T lymphocytes (CTL) generated from reovirus-infected mice infected with reovirus serotypes 1 or 3 [8], and to demonstrate that anti-reovirus CTL respond to the σ1 hemagglutinin [8]. Subsequent studies have confirmed a role for CTL in the anti-reovirus immune response [42,[51][52][53][54].…”
Section: Humoral and Cellular Immunity To Reovirusmentioning
confidence: 95%
See 1 more Smart Citation
“…Finberg and colleagues provided the first evidence that MHC-restricted, reovirus-specific cytotoxic T lymphocytes (CTL) generated from reovirus-infected mice infected with reovirus serotypes 1 or 3 [8], and to demonstrate that anti-reovirus CTL respond to the σ1 hemagglutinin [8]. Subsequent studies have confirmed a role for CTL in the anti-reovirus immune response [42,[51][52][53][54].…”
Section: Humoral and Cellular Immunity To Reovirusmentioning
confidence: 95%
“…The outer capsid consists of both structural and non-structural polypeptides [3,4]. The σ1 hemagglutinin, a structural capsid molecule, has been linked to many virus associated activities, including host cell attachment, viral neutralization by antibody, recognition by cytotoxic T cells, and tissue tropism and pathogenesis of reovirusmediated diseases [5][6][7][8][9][10][11][12][13][14][15][16]. Core proteins consist of transcriptases and replicases used in viral replication.…”
Section: Introductionmentioning
confidence: 99%
“…The outer capsid contains 3 polypeptides, μ1, σl, and σ3, which are encoded by genes of M2, S1, and S4, respectively (Weiner et al, 1978). The σl polypeptide is the viral hemagglutinin and has been linked to host cell attachment, type-specific neutralization, cytotoxic T cell recognition, tissue tropism, and pathogenesis of reovirus-mediated diseases (Finberg et al, 1979(Finberg et al, , 1982Lee et al, 1981;Weiner et al, 1977). Viral nonstructural proteins μNS (encoded by M3) and σNS (encoded by S3), as well as core protein μ2 (encoded by M1) play key roles in forming viral inclusions and recruiting other viral proteins and RNA to these structures for replication and assembly (Becker et al, 2001Broering et al, 2004;Mbisa et al, 2000;Parker et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…It is also the reovirus hemagglutinin (119) and elicits the formation ofneutralizing antibody (116). It is responsible for the development of delayed hypersensitivity (117) and for the generation of suppressor T cells (19) and of cytolytic T lymphocytes (18). It also determines the extent to which reovirus particles interact with microtubules (5) and specifies reovirus tissue tropism and virulence (115) (see below).…”
Section: Introductionmentioning
confidence: 99%